Analisis Penggunaan ChatGPT sebagai Media Pembelajaran dalam Kegiatan Belajar Siswa di MTs Raudlatul Hasaniyah Mojolegi Gading Probolinggo - Ulum, Moh Ulumuddin; Imam, Imam Bukhori; Shobirin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of Artificial Intelligence (AI) has significantly influenced educational practices, including the use of ChatGPT as a learning support tool. However, its implementation in Islamic Religious Education (IRE) remains limited and raises concerns regarding students’ learning independence, critical thinking, and academic ethics. This study aimed to analyze the use of ChatGPT as a learning medium in supporting students’ learning activities at MTs Raudlatul Hasaniyah Mojolegi, Gading, Probolinggo, to identify its benefits and challenges, and to examine its implementation from the perspective of Islamic Religious Education. This research employed a qualitative approach with a case study design. Data were collected through observations, semi-structured interviews, and documentation involving the principal, Islamic Religious Education teachers, and students. The data were analyzed using the interactive model of Miles and Huberman, including data condensation, data display, and conclusion drawing. The findings revealed that ChatGPT has been utilized as a supplementary learning medium to assist students in understanding learning materials, obtaining additional references, completing assignments, and promoting independent learning. The use of ChatGPT also increased students’ learning motivation and facilitated access to information. Nevertheless, excessive reliance on ChatGPT may reduce critical thinking skills, encourage plagiarism, and create dependency on AI-generated responses. From the perspective of Islamic Religious Education, ChatGPT can serve as an innovative learning medium provided that it is used responsibly, accompanied by teachers’ guidance, and aligned with the values of honesty, responsibility, and tabayyun (verification of information).